p53-dependent c-Fos expression is a marker but not executor for motor neuron death in spinal muscular atrophy mouse models - Buettner, Jannik M.; Sowoidnich, Leonie; Gerstner, Florian; Blanco-Redondo, Beatriz; Hallermann, Stefan; Simon, Christian M. (Frontiers in Cellular Neuroscience, 2022)
The activation of the p53 pathway has been associated with neuronal degeneration in different neurological disorders, including spinal muscular atrophy (SMA) where aberrant expression of p53 drives selective death of motor neurons destined to degenerate. Since direct p53 inhibition is an unsound therapeutic approach due carcinogenic effects, we investigated the expression of the cell death-associated p53 downstream targets c-fos, perp and fas in vulnerable motor neurons of SMA mice. Fluorescence in situ hybridization (FISH) of SMA motor neurons revealed c-fos RNA as a promising candidate. Accordingly, we identified p53-dependent nuclear upregulation of c-Fos protein in degenerating motor neurons from the severe SMNΔ7 and intermediate Smn2B/– SMA mouse models. Although motor neuron-specific c-fos genetic deletion in SMA mice did not improve motor neuron survival or motor behavior, p53-dependent c-Fos upregulation marks vulnerable motor neurons in different mouse models. Thus, nuclear c-Fos accumulation may serve as a readout for therapeutic approaches targeting neuronal death in SMA and possibly other p53-dependent neurodegenerative diseases.